(untitled) (Papeles, 2020)
A study was conducted about metacognitive skills reported by 118 university teachers in Bogotá through a metacognitive awareness inventory for teachers (MAIT). Based on the data collected, a validation of the instrument and the analysis of the correlation between some characterization variables of the teachers and the MAIT subcategories are carried out, as well as correlations between the own subcategories. In the analysis of the correlation of the sample is not evident that the variables of age, experience or studies have influence on the results reported by the teachers in the MAIT. In the analysis between the subcategories, the declarative knowledge and the ability to planning are the subcategories that most relate to others because their fundamental nature. On the other hand, a procedural knowledge and monitoring and evaluation skill seems to have little correlation with other subcategories because they tend to more practical processes.